Per una storia del pensiero geografico in Italia (1900-1950) - Matteo Proto (Projets de Paysage)
These paper focuses on defining a research project related to the history of Italian geography in the first half of the 20 century. Focusing especially on the period between the two World Wars, this study will fill the gap in current italian literature about the relations between geography, nationalism and imperialism. The aim is to compare Italian geography with other European schools in a transnational perspective, through the methodological approach of Histoire Croisée. Beside the analysis of the most important geographical works (particularly prominent is the research project on the Italian country house), this research will mainly use archive sources, to understand the complex cross of ideas, methodological approaches and scientific communication involving scholars of different countries.